[Afisz. Incipit] A. Dymsza, E. Dziewoński, I. Śmiałkowski, M. Załucki [...]. ([wydawca nieznany], 1965)
Afisz informujący o występach artystów i zespołu Wiktora Kolanowskiego w Hali Stoczni 7-8 września.